The Effect of the Financial Crisis on Investment Projects Case Study: Kurdistan Region of Iraq - Faiq, Amanj Jalal (Kurdistan Journal of Applied Research, 2021)
Domestic and international investments are critical for a country's economic growth since they facilitate the transfer of technology, job creation, increase the exports of goods, and services. The financial crisis in Kurdistan region has several economic consequences for domestic and foreign investments, especially on the investment projects throughout: the rate of capital, the numbers of projects, the rate of sectors distribution, nationality investors and the distribution of projects on governors. Since 2014, the Kurdistan region faced financial and economic crisis, which had a huge negative effect on investment projects. As a result, the influence of the investment projects of economic development suffered from fluctuation and instability. This study attempts to evaluate the effect of financial crises on investment projects in Kurdistan regional which are implemented by domestic and foreign investors. To accomplish this objective the statistical technique and economic analysis was applied for annual time series data from 2006 to 2017 by applying the compound annual growth rate Gordon growth model (CAGR). This study finds that the financial crisis has a huge negative effect on local and international investment initiatives.